Identification and treatment of older persons with sarcopenia. (December 2014) - Lauretani, Fulvio; Bautmans, Ivan; De Vita, Francesca; Nardelli, Anna; Ceda, Gian Paolo; Maggio, Marcello
Abstract In the last decades, sarcopenia in older persons has been operationalized by the assessment of lean body mass, muscle strength and/or physical performance. Several definitions of sarcopenia, using different parameters and cut-offs, have been proposed. However, which is the best definition to describe and to assess this condition is still matter of debate. Hand grip strength has been suggested as better predictor of incident mobility impairment and mortality, than skeletal muscle mass. In the light of the current knowledge, we sought to propose an operative approach for identifying and treating sarcopenic older persons according to main categories of sarcopenia: the age-related or primary sarcopenia and disease-related or secondary sarcopenia. We suggest that a quantitative assessment of grip strength alone might be sufficient to identify patients with primary sarcopenia. When chronic diseases accompany the ageing process, the combined assessment of muscle strength plus a balance test could be more appropriate. The identification of tests and pathological relevant cut-offs that facilitates the entry of sarcopenia into the clinical practice, could step forward researchers and physicians. This could be important for planning multidisciplinary models to maximize the maintenance of locomotive abilities especially in older persons affected by chronic diseases such as Parkinson's disease.